2008
DOI: 10.1002/gcc.20543
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of chromosomal gains as compared to DNA content changes is more useful to detect dysplasia in Barrett's esophagus brush cytology specimens

Abstract: Abnormal DNA ploidy status has been suggested as a prognostic factor for Barrett's esophagus progression into esophageal adenocarcinoma (EAC). The aim of the study was to compare image cytometry DNA analysis (ICDA) and fluorescent in situ hybridization (FISH) in the assessment of DNA ploidy status in Barrett's esophagus (BE), and to determine the value of these abnormalities as an adjunct to conventional cytology in detection of dysplasia and EAC. Brush cytology specimens of 90 BE patients were examined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 37 publications
(37 reference statements)
1
27
0
Order By: Relevance
“…Dysregulation of c-MYC has been implicated in BE carcinogenesis, 29,30 and its role as a biomarker in BE has been proposed both as an immunohistochemical marker 29,31 and as a fluorescence in situ hybridization probe to detect HGD. [32][33][34] No definite conclusions have yet been made, but previous studies along with this study highlight the importance of revisiting the role of c-MYC in Barrett's carcinogenesis.…”
Section: Discussionmentioning
confidence: 84%
“…Dysregulation of c-MYC has been implicated in BE carcinogenesis, 29,30 and its role as a biomarker in BE has been proposed both as an immunohistochemical marker 29,31 and as a fluorescence in situ hybridization probe to detect HGD. [32][33][34] No definite conclusions have yet been made, but previous studies along with this study highlight the importance of revisiting the role of c-MYC in Barrett's carcinogenesis.…”
Section: Discussionmentioning
confidence: 84%
“…However, the low sensitivity may be improved by staining for a biomarker specific for BE, and the use of immunohistochemistry, for example [59]. There have been a number of publications concerning the development of novel cytological biomarkers [60][61][62][63][64] for the assessment of dysplasia but few have been performed with the aim to diagnose BE since cytological sampling requires endoscopy.…”
Section: Potential Screening Methodsmentioning
confidence: 96%
“…One method which is being considered in relation to reducing endoscopic sampling error for dysplasia and OAC is the collection of brush cytology specimens, to improve sampling area, coupled with probes directed against chromosomal abnormalities. Using this FISH (fluorescence in situ hybridization)-based cytology approach coupled with probes directed against chromosomes 7 and 17, Rygiel et al [10] reported high sensitivity (85 %) and specificity (84 %) to detect and distinguish HGD (high-grade dysplasia)/OAC from LGD (low-grade dysplasia)/IND (indefinite dysplasia) and ND (no dysplasia) [10]. It is estimated that OAC develops in Barrett's oesophagus patients at a rate of approx.…”
Section: Biomarkers Of Disease Progressionmentioning
confidence: 99%